Representation of the Nature of Science in High School Physics Textbooks in Indonesia - Nurazmi, Nurazmi; Bancong, Hartono (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2025)
Understanding the Nature of Science (NoS) is widely acknowledged as a fundamental component of scientific literacy and an essential goal in physics education. Textbooks play a pivotal role in shaping students’ and teachers’ conceptions of science, particularly in educational contexts such as Indonesia, where they serve as the primary instructional resources. This study aimed to analyze how the ten aspects of NoS: empirical, inferential, creative, theory-driven, tentative, scientific method, scientific theories, scientific laws, the social dimension of science, and the social-cultural embeddedness of science are represented and presented in Indonesian high school physics textbooks. Using a descriptive content-analysis approach, five widely used 12th-grade textbooks were examined across five comparable topics: electromagnetic induction, alternating current, electromagnetic radiation, special relativity, and quantum phenomena. Each textbook was analyzed using the Abd-El-Khalick framework and scored on a −3 to +3 rubric to assess the explicitness and informedness of NoS representation.  The findings revealed that none of the textbooks entirely covered all ten NoS aspects; the social dimension of science was most frequently represented, while the creative, inferential, and tentative aspects were largely absent. The findings highlight the need for textbook authors and curriculum developers to integrate NoS aspects more explicitly to strengthen students’ understanding of scientific processes and reasoning. The results provide practical guidance for improving NoS representation in Indonesian physics textbooks and supporting the development of scientific literacy.